A study of tick infestation on cattle in the Abanico de Ibagué, Colombia using the complex systems approach (2015)
ABSTRACT: Cattle ranching systems have traditionally been studied based on Cartesian research models that break them down into each of their constitutive parts. For this reason, definition of biophysical and technical-productive parameters dominates knowledge in this area, but does not allow a complex vision of the production systems to be obtained. The emergence of agroecology and the implementation of new models of livestock rearing, such as silvopastoral systems (SPS), suggests that, in addition to studying the characteristics of the natural and technical-productive quantitative variables, sociocultural aspects should be incorporated to offer a more complex, transdisciplinary vision of agricultural systems and to allow new interpretations of agro-ecosystems, their components and interrelationships. The tick Rhipicephalus microplus has normally been considered a disruptor of the equilibrium of the ranching system, such that positivist research recommends its eradication. In this study, the structure and function of the system is related to a specific agricultural problem by describing the characteristics of a theoretical model to analyze tick infestation on cattle in the Abanico de Ibagué (Colombia), using the complex systems approach. Through development of this model, it was possible to postulate dynamic relationships between the SPS and conventional system components that can influence the behavior of the tick, demonstrating its presence in the system to be essential for achieving socioecological resilience.